PEDAGOGICAL FOUNDATIONS OF HERMENEUTIC COMPETENCE IN FUTURE TEACHERS - Nazirova, Shakhnozakhon (Oriental Journal of Education, 2026)
This article examines the pedagogical foundations for developing hermeneutic competence among prospective teachers based on contemporary theoretical and practical approaches. The study substantiates the effectiveness of a multi-stage hermeneutic analysis model, the integration of theoretical hermeneutics with practical training, and the use of situational tasks aimed at fostering students’ critical thinking. The structural components of hermeneutic competence content interpretation, pedagogical interpretation, and reflective analysis are identified as essential professional skills in teacher education.